2008
DOI: 10.1002/da.20402
|View full text |Cite
|
Sign up to set email alerts
|

Selective impairment in visual perception of biological motion in obsessive-compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is associated with a variety of well-documented cognitive deficits such as deficits in memory and executive functioning, but little is known about basic perceptual concomitants of OCD. This study investigated global, configural processing in OCD using dynamic (moving) and static stimuli with minimal demands on cognitive function. Twenty OCD patients and 16 age- and education-matched healthy control subjects were tested on four perceptual tasks: two motion tasks involved dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 70 publications
9
29
1
Order By: Relevance
“…Such an impairment was previously reported 28,29 , and our finding of an increased stimulus strength in high compulsives (see results) pointed towards a similar impairment.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Such an impairment was previously reported 28,29 , and our finding of an increased stimulus strength in high compulsives (see results) pointed towards a similar impairment.…”
Section: Methodssupporting
confidence: 91%
“…generally lower or higher ratings) and is independent of variability in perceptual decision making that can directly influence confidence ratings. The latter is of particular importance as OCD patients are reported to suffer from perceptual decision making difficulties 28,29 . By combining a computational model of metacognition together with experimentally controlled task difficulty, here we circumvent these limitations to single out contributing factors that selectively influence perceptual and metacognitive abilities 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Emotional activation has been found to be associated with the enhancement of visual perception (Phelps et al 2006), particularly in the ventral visual stream (Wright et al 2004), with evidence of an increased amygdala -visual cortex (extra striate and inferotemporal) functional connectivity for both pleasant and unpleasant stimuli (Sabatinelli et al 2005;Wendt et al 2011). In particular, several studies have revealed the existence of visual processing impairments in OCD, such as visual memory/visuomotor speed set shifting (Rampacher et al 2010), body posture discrimination (Shin et al 2013), and perception of biological movement (Kim et al 2008). In the present study, we observed that the activation of the defensive system was not associated with activity of the visual system, suggesting that patients with OCD are more sensible to threatening stimuli, rather to its physical characteristics.…”
Section: Discussioncontrasting
confidence: 49%
“…In accordance, evidence of specific visual processing deficits in OCD, namely in terms of visual organization (Rampacher et al 2010), and perception of biological movement (Kim et al 2008) has been documented, and suggesting alterations at the visual processing level.…”
Section: Introductionsupporting
confidence: 54%
“…For example, using fMRI, researchers have found that individuals with obsessive-compulsive disorder (an anxiety disorder characterized by serious anxiety and difficulty inhibiting thoughts) differ from healthy controls in terms of the brain areas they recruit while observing biological motion (Jung et al, 2009). Other researchers have found that individuals with obsessivecompulsive disorder perform poorer than healthy controls on biological motion perception tasks, but not on other non-biological motion perceptual tasks (Kim et al, 2008). Our study is the first to demonstrate that inhibitory ability may mediate the relationship between anxiety and the perception of biological motion stimuli, thus providing a rationale for the recruitment of other brain regions by more anxious populations.…”
Section: Discussionmentioning
confidence: 96%